Antioxidant-induced INrf2 (Keap1) tyrosine 85 phosphorylation controls the nuclear export and degradation of the INrf2–Cul3–Rbx1 complex to allow normal Nrf2 activation and repression - Kaspar, James W. (Company of Biologists, 2012)
INrf2 (Keap1) serves as a negative regulator of the cytoprotective transcription factor Nrf2. At basal levels, INrf2 functions as a substrate adaptor to sequester Nrf2 into the Cul3–Rbx1 E3 ligase complex for ubiquitylation and proteasomal degradation. In response to antioxidants, Nrf2 is released from the INrf2–Cul3–Rbx1 complex and translocates into the nucleus, where it activates ARE-mediated cytoprotective gene expression. The present studies demonstrate that INrf2, Cul3 and Rbx1 export out of the nucleus and are degraded during the early or pre-induction response to antioxidants. Mutation of Tyr85 in INrf2 stymied the nuclear export of INrf2, suggesting that tyrosine phosphorylation controls the pre-induction nuclear export and degradation in response to antioxidants. The nuclear export of Cul3–Rbx1 were also blocked when INrf2Tyr85 was mutated, suggesting that INrf2–Cul3–Rbx1 undergo nuclear export as a complex. INrf2 siRNA also inhibited the nuclear export of Cul3–Rbx1, confirming that Cul3–Rbx1 requires INrf2 for nuclear export. Newly synthesized INrf2–Cul3–Rbx1 is imported back into the nucleus during the post-induction period to ubiquitylate and degrade Nrf2. Mutation of INrf2Tyr85 had no effect on activation of Nrf2 but led to nuclear accumulation of Nrf2 during the post-induction period owing to reduced export and degradation of Nrf2. Our results also showed that nuclear export and degradation followed by the new synthesis of INrf2–Cul3–Rbx1 controls the cellular abundance of the proteins during different phases of antioxidant responses. In conclusion, the early or pre-induction nuclear export of INrf2 in response to antioxidants is controlled by tyrosine phosphorylation, whereas the nuclear export of Cul3 and Rbx1 is controlled by INrf2, allowing normal activation or repression of Nrf2.